Identification of novel therapeutic targets for blocking acantholysis in pemphigus. (21st September 2020) - Burmester, Imke A.K.; Flaswinkel, Sarah; Thies, Clara‐Sophie; Kasprick, Anika; Kamaguchi, Mayumi; Bumiller‐Bini, Valéria; Emtenani, Shirin; Feldmann, Nick; Kridin, Khalaf; Schmidt, Enno; van Beek, Nina; Zillikens, Detlef; et al.
Abstract : Background and Purpose: Pemphigus is caused by autoantibodies against desmoglein (Dsg) 1, Dsg3, and/or non‐Dsg antigens. Pemphigus vulgaris (PV) is the most common manifestation of pemphigus, with painful erosions on mucous membranes. In most cases, blistering also occurs on the skin, leading to areas of extensive denudation. Despite improvements in pemphigus treatment, time to achieve remission is long, severe adverse events are frequent and 20% of patients do not respond adequately. Current clinical developments focus exclusively on modulating B cell function or autoantibody half‐life. However, topical modulation of PV autoantibody‐induced blistering is an attractive target because it could promptly relieve symptoms. Experimental Approach: To address this issue, we performed an unbiased screening in a complex biological system using 141 low MW inhibitors from a chemical library. Specifically, we evaluated PV IgG‐induced Dsg3 internalization in HaCaT keratinocytes. Validation of the 20 identified compounds was performed using keratinocyte fragmentation assays, as well as a human skin organ culture (HSOC) model. key Results: Overall, this approach led to the identification of four molecules involved in PV IgG‐induced skin pathology: MEK1, TrkA, PI3Kα, and VEGFR2. Conclusion and Implications: This unbiased screening revealed novel mechanisms by which PV autoantibodies induce blistering in keratinocytes and identified new treatment targets for this severe and potentially life‐threatening skin disease.